Enhancing Risk Management Strategies: GAM Analysis of Health Insurance Claim Determinants - Wahyu, Azkanul; Ramdhani, Muhammad Dhafin Qinthar (Indonesian Operations Research Association (IORA), 2024)
Health insurance plays a crucial role in providing financial protection and ensuring access to necessary healthcare services. The awareness of Indonesian society regarding the importance of health insurance continues to grow, as evidenced by a 22% increase in premium income according to AAJI data as of March 2023. Despite the benefits of health insurance, an increasing number of insurance participants raises risks for insurance companies. The Generalized Additive Models (GAM) P-Spline can overcome these problems. The non-linear relationship between claim amount with age, body mass index, and blood pressure can be modelled with GAM P-Spline. The formed GAM model with PIRLS unable to give a clear information of relationship between variables explicitly, but can be seen by the shape of the function of each predictor associated with the link function used.